Biscuit's new trick - Capucilli, Alyssa Satin, 1957- (Capucilli, Alyssa Satin, 1957- Biscuit the little yellow puppy., 2000)
A puppy does all sorts of tricks in the process of learning the one his master is trying to teach him.